Benjamin Morrison: capstone - Morrison, Benjamin, artist (Colorado State University. Libraries, 2015)
The artist's statement: In this collection of works I am exploring an idea of a kind of role reversal between the mind and the body. In the world we live in there is a priority in the physical. The mental processes of an individual has a clear influence on the physical actions that they employ but does not seem to have a direct influence on the world in the way that the physical does. In these works I have created a reality where the mind does have this direct influence on the physical. The physical form of these characters is entirely controlled by the mental state that is most prominent in the actor's system of beliefs.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.